1987
DOI: 10.1159/000100733
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Mesencephalotomy versus Multiple Thalamotomies in the Treatment of Chronic Cancer Pain Syndromes

Abstract: Two neurosurgical centers, Bologna (Italy) and Freiburg (FRG), have compared results obtained with stereotactic mesencephalotomy (SM; Bologna) and multiple thalamotomies (MT; Freiburg) in the surgical treatment of chronic cancer pain syndromes. In total, 161 patients were operated, 109 in Bologna and 52 in Freiburg. In SM the lesions were single and centered on the spinothalamic tract at the mesencephalic level, while in MT the lesions were multiple in the thalamic nuclei (ventrocaudal parvocellular nucleus, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Secure diagnosis allows identification of tumors for which resection is more feasible and beneficial. In one stereotactic biopsy study of thalamic lesions, 48 approximately 18% of cases were actually nonneoplastic. One particularly important subset of thalamic tumors to identify is the malignant diffuse midline glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Secure diagnosis allows identification of tumors for which resection is more feasible and beneficial. In one stereotactic biopsy study of thalamic lesions, 48 approximately 18% of cases were actually nonneoplastic. One particularly important subset of thalamic tumors to identify is the malignant diffuse midline glioma.…”
Section: Discussionmentioning
confidence: 99%
“…The work of Mark and colleagues led to the belief that targeting the medial thalamic nuclei was more effective in managing pain. Frank and coauthors reported the overall success rate of medial thalamotomy to be 52%, 6 with cancer pain being the main condition treated. Several pain syndromes, including cancer pain, central and peripheral deafferentation pain, spinal cord injury, malignancy, arthritis, and the neurogenic pains associated with Parkinson's disease, 5 have been successfully treated by medial thalamotomy.…”
Section: Medial Thalamotomymentioning
confidence: 99%
“…Frank and colleagues reported a 60% rate of pain relief following medial thalamotomy by targeting multiple sites within the medial thalamus (including Vcpc, CM, nucleus limitans, and lamella medialis). 42 Tasker reported a 46% incidence of nociceptive pain relief and a 29% incidence of neuropathic pain relief. 43 Although medial thalamotomy affords a lower efficacy rate in these two studies than that reported for stereotactic mesencephalotomy (85% for nociceptive cancer pain 44 ; see later), the indications for medial thalamotomy are broader and the potential morbidity and mortality are less.…”
Section: Outcomementioning
confidence: 99%